Using Computer Simulation for Teaching Mechanics Concept - Gunawan Gunawan; Lovy Herayanti; Imran Imran; Habibi Habibi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
Computer technology presents opportunities and innovations in physics learning. Some of the concepts of physics are abstract concepts. Learning abstract concepts requires appropriate media assistance. In this research, we have developed some computer simulations to support the learning concept of mechanics. The study aimed to examine the effectiveness of computer simulation in students’ understanding of mechanics. The sample used is students from the department of physics education who took a mechanics course at University of Mataram. Data were collected using multiple-choice and essay tests and then analyzed quantitatively. Data analysis used the ANAVA test and N-gain score. The result of the research shows the influence of computer simulation on students’ understanding of the concept of mechanics. Improvement occurs in all sub-materials of mechanics. The average for the concept mastery of students in the experimental group is higher than that of the control group. Statistically, the difference in the increase in the concept mastery between the two groups did not significantly differ. The improvement in students' concept of learning using computer simulation was higher than the control group who studied conventionally.